Huguenot Networks, 1560-1780: The Interactions and Impact of a Protestant Minority in Europe - Larminie, Vivienne (Routledge, 2017)
"Cover" -- "Title" -- "Copyright" -- "Contents" -- "List of Figures" -- "List of Tables" -- "List of Abbreviations" -- "Acknowledgements" -- "Introduction" -- "1 Thinking with Calvinist Networks: From the âCalvinist Internationalâ to the âVenice Affairâ (1608â1610)" -- "2 London, Nerve Centre of the Huguenot Diplomatic Network in the Later Sixteenth Century" -- "3 The Herbert Connection, the French Church and Westminster Politics, 1643â1661" -- "4 Abel Boyer and Other Huguenot Reporters of Parliament: Hansard Avant la Lettre?" -- "5 Information Professionals: Huguenot Diplomats in Later Stuart London and Their European Context" -- "6 Overcoming the Conformist/Nonconformist Divide: Huguenot Networking in Later Stuart London" -- "7 Choosing the Path to Exile: Networks, Destinations and Determinants" -- "8 Alexandre Sasserie of Paris, London and Thorpe-le-Soken: A Man of Trust in the Refuge" -- "9 Huguenot and Nonconformist Networks: Philip Dupont in Late Stuart Suffolk" -- "10 West Coast Connections: The Correspondence Network of Ãlie BouhÃ©reau of La Rochelle" -- "11 Financial Networks and the Payment of Military Pensions, 1692â1720" -- "12 The Early Huguenot Community of Dublin and Its Networks" -- "13 English Relief Activities for Continental Protestants in the Eighteenth Century: Perpetuating Religious Networks in the Age of Reason" -- "Glossary" -- "Contributors".